AVAILABILITY OF HEALTHCARE FACILITIES IN UKRAINE PROVIDING MENTAL HEALTH SUPPORT TO PATIENTS AFFECTED BY THE WAR - Ivan S. Chervynskyy; Nataliia Yu. Kondratiuk (Клінічна та профілактична медицина)
Introduction. War and armed conflicts have a profound impact on the mental health of populations, increasing the prevalence of trauma-related disorders and burdening healthcare systems. This study assesses the availability of mental health facilities for patients affected by the war in Ukraine, highlighting current capabilities, regional disparities, and barriers to accessing care.